Direct-Driver Wind Turbine Model: A Bond Graph Approach - America Torres-Tinoco; Roberto Tapia-Sanchez; Aurelio Medina-Rios (IEEE Access, 2025)
This paper presents a comprehensive Bond Graph (BG) model for a Direct-Drive Wind Turbine (DDWT) that captures the energy interactions among aerodynamic, mechanical, and electromechanical subsystems. The model includes the blades, hub, bearings, shaft, and Permanent Magnet Synchronous Generator (PMSG), and is parameterized using real data from a 3 kW horizontal-axis turbine designed for residential applications. A key aspect of the proposed approach is the accurate representation of bearing dynamics within a modular, physically consistent, and multidomain framework. The modelling strategy seeks a balance between physical realism, coherent energy structuring, and computational feasibility. The aerodynamic response was characterized using a realistic blade profile, and the performance of the system was validated through a series of simulations under different operating conditions. The model was designed to support system-level analysis and serves as a foundation for future integration with control strategies, condition monitoring, and fault diagnosis schemes. By integrating components that are often treated in isolation, such as the rotor–bearing interaction, into a unified BG-based structure, this study advances the use of Bond Graphs in the modeling of wind energy conversion systems. The resulting model is reusable, scalable, and suitable for studies involving both transient and steady-state behaviors of small-scale wind turbines.